Association between Intimate Partner Violence, Knowledge and Use of Contraception in Africa: Comparative Analysis across Five African Regions - Rafeek A. Yusuf, MBBS, MPH, MS; Deepa Dongarwar, MS; Zenab I. Yusuf, MBBS, MPH; Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2019)
Background Or Objectives: Intimate partner violence (IPV) against women is common globally, and is associated with several adverse consequences. This study provides a comparative analysis of potential regional differences in the association between IPV and knowledge and use of contraceptives within Africa. Methods: A multi-country cross-sectional study was conducted using data on women of reproductive age 15-49 years from the Demographic and Health Surveys covering five African regions. Exposure and outcome variables were IPV and reproductive literacy (comprising modern contraception knowledge and contraception usage) respectively. We used survey log-binomial regression models to generate prevalence ratios that estimated the association between IPV versus knowledge and usage of modern contraception. Results: Overall IPV prevalence in Africa was 30.8% with notable regional differences. Demographic, socioeconomic, and reproductive history markers of IPV were more pronounced in younger women, rural residents, women of low socioeconomic status and those with copious knowledge but poor usage of modern contraception. The level of knowledge of contraception was 84% greater among African women who were victims of IPV compared to their counterparts who were not victims of IPV (p < 0.0001). IPV was not associated with actual usage of modern contraception (p = 0.21). Conclusion And Global Health Implications: IPV against women in Africa may incentivize knowledge seeking of modern contraception as protective mechanisms. Regional variations notwithstanding, understanding the existing and new characteristics predictive of IPV may inform policy development, resource allocation and prevention of IPV globally. Key words: • Violence • Women • Contraception; • Knowledge • Usage • Africa • Intimate partner violence • Demographic and health surveys • Benin • Burundi • Egypt • Kenya • South Africa   Copyright © 2020 Yusuf et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.